Analysis of Halal Fashion Business Development Strategies in Medan City - Nasution, Hafizah Mahira; Rahma, Tri Inda Fadhila; Inayah, Nurul (Universitas Muhammadiyah Sorong, 2025)
The halal industry continues to be an important issue in Indonesia, including in Medan City. This study aims to analyze the development strategy of Umama Gallery Medan halal fashion and formulate effective alternative strategies by analyzing internal and external factors to face competition in the Halal Fashion industry in Medan City. This research uses mixed-method methodology by using SWOT analysis and QSPM approaches. The results of this study indicate that the SWOT analysis of Umama Gallery Medan is in quadrant I which supports aggressive strategies so that the suitable strategy used is the SO (Strength - Oppurtunity) strategy 1) Develop product variations in accordance with Muslim fashion trends to remain competitive, 2) Expand marketing through e-commerce platforms, and 3) Increase collaboration with influencers and hijabers communities to strengthen brand image. And QSPM analysis, obtained alternative strategies that are suitable for Umama Gallery Medan, namely ST (Strength - Threat) 1) Increase product innovation regularly to anticipate changes in fast fashion trends, 2) Maintain product quality to remain superior to competitors in the midst of intense market competition. The most appropriate alternative strategy for Umama Gallery Medan is the S-O (Strength-Opportunities) strategy with an aggressive growth approach. This strategy includes the development of product variations that align with Muslim fashion trends to maintain competitiveness in the market.